Effects of wetted inner clothing on thermal strain in young and older males while wearing ventilation garments - Tokizawa, Ken (Frontiers in Physiology, 2023)
The present study examined the effect of wearing a water-soaked inner t-shirt with a ventilation garment on thermal and cardiovascular strain in eight young (26 ± 4 y) and eight older (67 ± 3 y) men undertaking moderate-intensity work (metabolic rate: 200−230 W m-2) in a hot environment (37 °C, 50% RH, 2.8 kPa). While intermittent walking in hot conditions for 60 min, as a control (CON), the subject wore a dry inner t-shirt (long-sleeved) without fanning of a ventilation jacket (single-layered cotton, 0.21 clo). On separate days, under a fanned ventilation jacket, the subject wore a dry inner t-shirt (DRY) or an inner t-shirt soaked with 350 mL of tap water (WET). In the young group, increases in rectal temperature from pre-exercise baseline in the WET trial (0.7 ± 0.2 °C) were lower than in the CON (1.3 ± 0.3 °C) and DRY (1.1 ± 0.2 °C) (both p<0.05) trials during exercise in hot conditions. In the older group, the increases were also attenuated in WET (0.7 ± 0.4 °C) compared with CON (1.3 ± 0.4 °C)and DRY (1.1 ± 0.4 °C) (both p<0.05) without differences between age groups. Heart rate and whole-body sweat loss were lowest in the WET, followed by DRY, and then CON conditions in both groups (all p<0.05). These findings demonstrate that wearing a water-soaked inner t-shirt while using a ventilation garment is an effective and practical cooling strategy to mitigate thermal and cardiovascular strains in young and older individuals during moderate-intensity work in hot conditions.